2013
DOI: 10.1007/978-3-642-40498-6_17
|View full text |Cite
|
Sign up to set email alerts
|

One Half or 50%? An Eye-Tracking Study of Number Representation Readability

Abstract: Abstract. Are numbers expressed as digits easier to read and understand than written with letters? What about fractions and percentages? Exact or rounded values? We present an eye-tracking study that attempts to answer these questions for Spanish, using fixation and reading time to measure readability as well as comprehension questions to score understandability. We find that digits are faster to read but do not help comprehension. Fractions help understandability while percentages help readability. No signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
3
2

Relationship

4
4

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 33 publications
0
23
0
Order By: Relevance
“…Rello et al (2013a) used eye tracking to investigate cognitive load associated with different forms of number representation, and how different conditions affected understandability and readability for dyslexics. They found that numbers presented as digits were more readable than digits presented as words, and that percentages were faster to read than fractions.…”
Section: Visual Search and Eye Movement Measuresmentioning
confidence: 99%
“…Rello et al (2013a) used eye tracking to investigate cognitive load associated with different forms of number representation, and how different conditions affected understandability and readability for dyslexics. They found that numbers presented as digits were more readable than digits presented as words, and that percentages were faster to read than fractions.…”
Section: Visual Search and Eye Movement Measuresmentioning
confidence: 99%
“…fantabulous [11], words with errors [9], non-words, 9 e.g. happisfaction [9], and numerical expressions [40]. In the experimental design we did not use words of such characteristics to control other possible effects.…”
Section: Word Frequency and Length In Dyslexiamentioning
confidence: 99%
“…In this way, a visitor can now contemplate paintings and sculptures that, for the first time, are exposed in the gallery. (h) one text has two numerical expressions (Rello et al, 2013b) and the other has two foreign words (Cuetos and Valle, 1988), both being elements of similar difficulty; and (i) have the same number of highlighted keyphrases.…”
Section: Methodsmentioning
confidence: 99%